IMPACT OF COVID-19 ON SPORT INDUSTRY IN THAILAND - Chankuna, Dittachai; Chanthonsarasom, Assawin; Inchana, Kannika; Sukdee, Thitipong; Sriboon, Nilmanee (Academic Journal of Thailand National Sports University, 2021)
COVID-19 pandemic was inducing a large impact in sport industry management. This article was aimed to study the spreading impact of COVID-19 on sport industry in Thailand and to propose Thailand sport industry managing practice based on sport ecosystems concept. Data collection consist of reviewing of literatures and interviewing. The result was found that sport industry in Thailand, which categorized into 5 groups named; Sports and exercise, Professional sports, Educational and sports science, Sport tourism and Sport product entrepreneur, have organizational rapidly change in terms of technology or Digital transformation. Managing of Thailand sport industry based on sport ecosystems could sustainably prepare for future change in 3 areas; organizational developing to support New normal for effectiveness, developing for innovation or best management and integrating all stakeholders.